KEMAMPUAN GURU DALAM MELAKSANAKAN KETERAMPILAN MENJELASKAN (Di TK Witri 2 Kota Bengkulu) - Yulia Wulandari; Nina Kurniah; Delrefi D. Delrefi D. (Universitas Bengkulu, 2018)
This study aims to describe the ability of teachers in implementing the skills explain in kindergarten Witri family 2 city of Bengkulu. The method used is descriptive quantitative. The subject of this research totalled 5 kindergarten teachers teachers consisting of 2 teachers 1 TPA, principals and teachers of teachers 2 B1 and B2 of the TK Witri family 2 of the city of Bengkulu. The technique of collecting data through observation in the form of a checklist. Data analysis techniques used on average and ending value. Research results show that skills explain the kindergarten teacher at Witri family 2 is on the category either. It is therefore suggested by teachers to be able to maintain and enhance the skills Explain the so can make the kids don't get bored at the moment of learning takes place.